2021
DOI: 10.4103/aja.aja_76_20
|View full text |Cite
|
Sign up to set email alerts
|

A decrease of docosahexaenoic acid in testes of mice fed a high-fat diet is associated with impaired sperm acrosome reaction and fertility

Abstract: Obesity is a major worldwide health problem that is related to most chronic diseases, including male infertility. Owing to its wide impact on health, mechanisms underlying obesity-related infertility remain unknown. In this study, we report that mice fed a high-fat diet (HFD) for over 2 months showed reduced fertility rates and increased germ cell apoptosis, seminiferous tubule degeneration, and decreased intratesticular estradiol (E2) and E2-to-testosterone ratio. Interestingly, we also detected a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Our study also found a positive relationship between DPA and disrupted acrosome rate. The same condition was revealed in mice, where a decrease in DPA was associated with impaired acrosome reaction, resulting in negative consequences for fertilization ( 41 ).…”
Section: Discussionmentioning
confidence: 59%
“…Our study also found a positive relationship between DPA and disrupted acrosome rate. The same condition was revealed in mice, where a decrease in DPA was associated with impaired acrosome reaction, resulting in negative consequences for fertilization ( 41 ).…”
Section: Discussionmentioning
confidence: 59%
“…(Patterson et al, 2014). The fatty acids level (Bunay et al, 2021), especially DHA, are associated with spermatogenesis (Hale et al, 2019). A high-fat diet (HFD) induces disruption of the gut microbiome, as reflected by decreases in Bacteroides and increases in Firmicutes and Aspergillus in mice models (Hildebrandt et al, 2009;Graham et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that the different types of diet patterns based on saturated, monounsaturated, or polyunsaturated fatty acids may induce alterations in gut microbiota composition (Patterson et al, 2014 ). The fatty acids level (Bunay et al, 2021 ), especially DHA, are associated with spermatogenesis (Hale et al, 2019 ). A high-fat diet (HFD) induces disruption of the gut microbiome, as reflected by decreases in Bacteroides and increases in Firmicutes and Aspergillus in mice models (Hildebrandt et al, 2009 ; Graham et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although not all obese male individuals necessarily have impaired reproductive ability, the clinical data showed that nearly 80% of male patients with reproductive disorders are classified as overweight or obesity [ 10 ]. Obesity adversely affects male reproduction, including spermatogenesis in the testis and the subsequent sperm maturation process in the epididymis, leading to decreased sperm concentration, abnormal morphology of the sperm, impaired sperm motility and fertilizing capacity [ 3 , 37 , 38 ]. Previous studies reported that obesity affected the activity of the hypothalamic–pituitary–testis axis, thus damaging spermatogenesis [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%